2022
DOI: 10.1101/2022.01.27.22269435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of low relative skeletal muscle mass and power on the development of metabolic syndrome in Japanese women: a 7-year prospective study

Abstract: Previous cross-sectional studies indicated that low relative skeletal muscle mass against body weight (appendicular lean mass divided by body weight, ALM/Wt or divided by body mass index, ALM/BMI) was negatively associated with metabolic syndrome (MetS). The aim of this longitudinal study was to investigate the impact of low relative skeletal muscle mass and leg muscle power on the development of MetS in Japanese women in a 7-y prospective study. Subjects were 346 Japanese women aged 26 to 85 years. The refere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In accordance with our results, it has been reported that Low-MQI is associated with a cluster of MetS markers that included SBP and elevated WC [55]. In addition, another study reported that low relative skeletal muscle was associated with a higher risk of MetS [40]. Another retrospective cohort study indicated that low muscle quality and quantity incremented the incidence of MetS [56].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our results, it has been reported that Low-MQI is associated with a cluster of MetS markers that included SBP and elevated WC [55]. In addition, another study reported that low relative skeletal muscle was associated with a higher risk of MetS [40]. Another retrospective cohort study indicated that low muscle quality and quantity incremented the incidence of MetS [56].…”
Section: Discussionsupporting
confidence: 92%
“…In this sense, recent evidence indicated that MetS markers such as blood pressure and fasting blood glucose were linked with muscle strength and physical fitness [12]. Yamada et al [40] found a longitudinal link between low skeletal muscle and the development of MetS. In a complementary way, it has been shown that obese subjects had a high prevalence of poor MQI [41], and poor muscle quality can lead to the development of MetS [42].…”
Section: Introductionmentioning
confidence: 99%